The Ripple Effect of Work Family Conflict: Examining Parenting Stress in Dual-Earner Families with School-Aged Children - Rizal, Gumi Langerya; Govindasamy, Priyalatha; Fikry, Zulian; Duryati, Duryati (Fakultas Agama Islam Universitas Ibn Khaldun Bogor, 2024)
Balancing work and family life is a significant challenge for dual-income families, particularly for parents with elementary school-aged children. This study investigates the cross-relationship between work-family conflict (WIF and FIW) experienced by husbands and parenting stress experienced by wives in dual-income families. Utilizing a quantitative survey design, data were collected from 246 dual-income couples with school-aged children. The findings reveal that WIF experienced by husbands significantly increases the parenting stress of wives, while FIW experienced by husbands does not show a significant effect. These results highlight the importance of considering the interactive dynamics within dual-income families and the need for supportive measures to mitigate the negative impacts of work-family conflict on overall family well-being.